Does Aggressive Surgery Improve Outcomes? Interaction Between Preoperative Disease Burden and Complex Surgery in Patients With Advanced-Stage Ovarian Cancer. Issue 6 (June 2015) - Horowitz, Neil S.; Miller, Austin; Rungruang, Bunja; Richard, Scott D.; Rodriguez, Noah; Bookman, Michael A.; Hamilton, Chad A.; Krivak, Thomas C.; Maxwell, G. Larry
<x xml:space="preserve">Abstract</x> ABSTRACT Most patients with epithelial ovarian cancer (EOC) are diagnosed at an advanced stage, and 5-year survival is low. Initial management includes primary debulking surgery (PDS) followed by adjuvant platinum and taxane-based chemotherapy. A large number of studies have shown a survival benefit for patients with advanced EOC after PDS from both optimal debulking (<1 cm of residual disease [MR]) and complete surgical resection (R0). Several studies have suggested a worse prognosis for patients with extensive preoperative disease despite optimal debulking. There has been a growing trend in the last decade toward more aggressive PDS (complex surgery) to minimize residual disease and optimize outcome in patients with widespread disease. The relationship between the initial disease burden or disease distribution and surgical complexity to achieve optimal debulking is poorly understood. Because of the lack of randomized controlled trials, it is unclear whether aggressive surgical cytoreduction can overcome the negative impact of a high preoperative disease outcome and extend survival. The aim of this study was to examine the impact of preoperative disease burden, complex surgery, and extent of residual disease (MR or R0) after PDS on progression-free (PFS) and overall survival (OS) in patients with advanced EOC or primary peritoneal cancer (PPC). All data on demographics and pathology as well as surgical and patient outcomes were abstracted from 2655 patients with EOC or PPC enrolled in the Gynecologic Oncology Group 182 study. The effects of disease distribution (preoperative disease score [DS]), complexity of surgery (complexity score [CS]), and extent of residual disease (MR or R0) after PDS on PFS and OS were analyzed using the Kaplan-Meier method and multivariable regression analysis. The DS was developed based on initial site of disease and complexity of surgery during PDS; the score was classified as DS low, moderate, or DS high. The CS was calculated using a published scoring system and was classified as CS low, moderate, or high. Following primary surgery, the prognosis was worse among patients with MR than among patients with R0 (PFS, 15 vs 29 months; P < 0.01; OS, 41 vs 77 months; P < 0.01). Patients with high preoperative disease burden (DS high) had shorter PFS and OS than did those with DS moderate or low (PFS, 15 vs 23 or 34 months [P < 0.01]; OS, 40 vs 71 or 86 months [P < 0.01], respectively). This relationship was maintained in the subset of R0 patients with PFS (18 vs 33 months; DS moderate or low: P < 0.001) and OS (50 vs 83 months; DS moderate or low: P < 0.001). Complexity score was not an independent prognostic indicator of either PFS or OS after controlling for DS, as well as performance status, age, and cell type. These data show that initial disease burden remains a significant prognostic indicator for PFS and OS despite R0. Survival is not improved by complex surgery after adjusting for confounding influences, especially residual disease.